2012
DOI: 10.3109/01942638.2011.644032
|View full text |Cite
|
Sign up to set email alerts
|

Passive Range of Motion in a Population-Based Sample of Children with Spastic Cerebral Palsy Who Walk

Abstract: While passive range of motion (PROM) is commonly used to inform decisions on therapeutic management, knowledge of PROM of children with spastic cerebral palsy (CP) is limited. A population-based sample of 178 children with spastic CP (110 male; unilateral, n = 94; bilateral, n = 84; age range 4-17 years) and 68 typically developing children (24 male; age range 4-17 years) were recruited to the study. All children were able to walk a minimum of 10 m over a straight flat course, with or without assistive devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 15 publications
2
31
0
2
Order By: Relevance
“…Previously, this mutant rat model has been used for neural studies exclusively (7,39,44). The mechanical properties of the spastic rat calf muscles found in the present study are consistent with the reduced functional range of motion and increased stiffness reported clinically in human limbs affected by spasticity (17,31,32,40), and the narrower active lengthforce curves estimated in in vivo studies on human GA (2,15,16). Thus the spastic rat model used in the present study mimics several important features of spasticity in human patients, and may be used to elucidate the mechanisms responsible for changes in muscle and limb mechanical properties observed in patients with spasticity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previously, this mutant rat model has been used for neural studies exclusively (7,39,44). The mechanical properties of the spastic rat calf muscles found in the present study are consistent with the reduced functional range of motion and increased stiffness reported clinically in human limbs affected by spasticity (17,31,32,40), and the narrower active lengthforce curves estimated in in vivo studies on human GA (2,15,16). Thus the spastic rat model used in the present study mimics several important features of spasticity in human patients, and may be used to elucidate the mechanisms responsible for changes in muscle and limb mechanical properties observed in patients with spasticity.…”
Section: Discussionsupporting
confidence: 80%
“…muscle spasticity; mechanical properties; myofascial force transmission; muscle stiffness MUSCLE SPASTICITY HAS BEEN defined as a "velocity-depended resistance to stretch" (24) and arises secondary to upper motoneuron lesions with cerebral palsy and stroke as the most common examples (12). Individuals suffering from spasticity typically experience muscle weakness, enhanced joint stiffness, increased muscle tone, reduced range of joint motion, increased antagonistic co-contraction, and exaggerated reflexes (1,3,6,12,13,32,41,48). These effects severely impair the ability to perform daily activities, and treatment is often needed.…”
mentioning
confidence: 99%
“…This is despite the developers' original paper describing it as a classification system . The GMFCS is an important predictor of the risk of scoliosis and hip dysplasia in CP and may be linked to success of some surgeries, reduction in muscle strength, and changes in range of motion over time . Given the importance of the GMFCS for many surgical outcomes, the authors believe that its use to classify study participants should become a requirement for publication of orthopaedic outcomes of lower limb surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, the adductor muscles did not lose ROM with age, which is common in children with spastic diplegic CP. 10,38 The longitudinal data published by Nordmark et al 10 show that for measurements such as hip abduction and the popliteal angle, there can be a considerable change during the early years, with the mean ROM of hip abduction decreasing from 43 • to 34 • , between age 2 and 14 years. McDowell et al 38 found significant reductions in passive ROM for the hamstrings and hip adductor musculature in children with spastic CP.…”
Section: Discussionmentioning
confidence: 97%
“…The mean of hip abduction in children of 4 to 10 years at GMFCS level III was 25.9 • ± 9.5 • . 38 These children also had no history of lower limb surgery.…”
Section: Discussionmentioning
confidence: 97%